Evaluation of the Influence of Recycled Polypropylene on the Rutting Resistance of Asphalt Layers - Toro, Karol Alexia Puelles (2023)
Rutting or rutting in asphalt pavements is one of the most frequent failures and is due to excessive stress to which the inner layers are subjected. Due to this problem, a way to increase rutting resistance was developed in this research. Therefore, mixtures of conventional asphalt were prepared with the addition of polypropylene, obtained from recycled face masks, in percentages of 0.5%, 1.0% and 1.5%. The polypropylene functions as a binding agent. Based on the results of the study, the mixture that had 0.5% of fibers presented a slight increase in stability compared to the conventional mixture, while in the other mixtures the stability decreased, since the percentage of voids increased. Likewise, the value of the modulus of elasticity, which was not obtained in the laboratory tests, was found by means of a computational simulation (ANSYS). This value is necessary to obtain the rutting generated in each asphalt mixture. Finally, the rutting is obtained by means of a computational simulation of the Hamburg Wheel test. From the rutting test results, the polypropylene-modified blends showed good resistance to deformation, reducing the rutting from 4.87 mm to 1.03 mm as the percentage of polypropylene increased from 0% to 1.5%.